2018
DOI: 10.3892/etm.2018.6489
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin is able to alleviate TGF‑β‑induced fibrosis in renal tubular epithelial cells by suppressing miR‑21

Abstract: Patients with chronic kidney disease (CKD) are characterized by a gradual loss of kidney function over time. A number of studies have indicated that tubule interstitial fibrosis (TIF) is associated with the occurrence and development of CKD. The aim of the present study was to investigate the effect of quercetin treatment on the fibrosis of renal tubular epithelial cells and to determine whether the anti-fibrotic effects of quercetin are achieved via microRNA (miR)-21. Human tubular epithelial HK-2 cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…Gao et al found that the cardiac anti-fibrotic effect of isorhamnetin, a quercetin methylated metabolite, occurs due to blockage of the Pi3k/Akt/mTor signaling pathway [48]. Cao et al found that quercetin is able to reduce the TGF-βinduced fibrotic process in human tubular epithelial HK-2 cells through miR-21 suppression and PTEN upregulation [49]. Zhang et al in an in vitro study of the imatinib-resistant chronic myeloid leukemia cell line K562 (K562R IMT ) demonstrated the inhibitory effect of dasatinib on the Pi3k/Akt/mTor signaling pathway and observed a slight upregulation of Pten at high doses of the drug [50].…”
Section: Agingmentioning
confidence: 99%
“…Gao et al found that the cardiac anti-fibrotic effect of isorhamnetin, a quercetin methylated metabolite, occurs due to blockage of the Pi3k/Akt/mTor signaling pathway [48]. Cao et al found that quercetin is able to reduce the TGF-βinduced fibrotic process in human tubular epithelial HK-2 cells through miR-21 suppression and PTEN upregulation [49]. Zhang et al in an in vitro study of the imatinib-resistant chronic myeloid leukemia cell line K562 (K562R IMT ) demonstrated the inhibitory effect of dasatinib on the Pi3k/Akt/mTor signaling pathway and observed a slight upregulation of Pten at high doses of the drug [50].…”
Section: Agingmentioning
confidence: 99%
“…Both rhamnetin and cirsiliol induced radio‐senitization and inhibited EMT by miR‐34a/Notch1 signaling in non–small‐cell lung cancer cells . Quercetin alleviated TGF‐β1‐induced fibrosis in HK‐2 cells via downregulating miR‐21 expression and upregulating PTEN and TIMP metallopeptidase inhibitor 3 (TIMP3) expression . Sophocarpine from Sophora alopecuroides L. inhibited tumor progression and reversed EMT by targeting miR‐21 in head and neck cancer .…”
Section: Small Molecules Against Emtmentioning
confidence: 99%
“…40 Quercetin alleviated TGF-β1-induced fibrosis in HK-2 cells via downregulating miR-21 expression and upregulating PTEN and TIMP metallopeptidase inhibitor 3 (TIMP3) expression. 45 Sophocarpine from Sophora alopecuroides L. inhibited tumor progression and reversed EMT by targeting miR-21 in head and neck cancer. 51 In addition, sophocarpine exerted a profound antitumor effect through inhibiting EMT induced by TGF-β.…”
Section: Ras Signaling Pathwaymentioning
confidence: 99%
“…Several miRNA molecules were expressed with a common pattern among in vitro and in vivo experiments as a result of quercetin treatment. miR-21 in particular was deregulated in the same manner (downregulation) in MCF-7, BEAS-2B and HK-2 cell lines and in two in vivo models (mouse/ rat) [67][68][69]81 . The literature search identified a few exceptions in two articles that reported quercetin mediated upregulation of miR-21 in the majority of samples 65,84 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, important information is missing in the paper, e.g. duration of incubation during selected experiments 69 .…”
Section: Mir-21mentioning
confidence: 99%